HAK DAN KEWAJIBAN PEREMPUAN DALAM PERSPEKTIF SYARIAT ISLAM - Asman Asman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Islam has its own views regarding women's equality. For example, it can be seen from the more prudent and far-sighted Islamic efforts to strive for women's equality on the one hand without eliminating that womanly nature on the other. Islamic society in this and other problems, is subject to what has been stipulated by Islamic law. Based on the above problems, what needs to be studied in this paper is how women are in the perspective of Islamic law, as the main study is the source of the law, rights and obligations of women in Islamic law. This study uses a literature approach that discusses relevant books on feminism and is filtered in Islamic law or sharia. This study concludes that in relation to the rights that women have, having a special responsibility to be implemented is not the same as that of men.